Immunometabolic Regulation of Interleukin-17-Producing T Helper Cells: Uncoupling New Targets for Autoimmunity - Binger, Katrina J.; Côrte-Real, Beatriz F.; Kleinewietfeld, Markus (Frontiers in Immunology, 2017)
IL-17 producing T helper cells (Th17) are critical for the host defence of bacterial and fungal pathogens, but also play a major role in driving pathogenic autoimmune responses. Recent studies have indicated that the generation of Th17 cells from naïve CD4+ T cells is coupled with massive cellular metabolic adaptations, necessary to cope with different energy and metabolite requirements associated with switching from a resting to proliferative state. Furthermore, Th17 cells have to secure these metabolic adaptations when facing nutrient-limiting environments, such as at the sites of inflammation. Accumulating data indicates that this metabolic reprogramming is significantly linked to the differentiation of T helper cells, and particularly, that the metabolic changes of Th17 cells and anti-inflammatory FOXP3+ regulatory T cells (Tregs) are tightly and reciprocally regulated. Thus, a better understanding of these processes could offer potential new targets for therapeutic interventions for autoimmune diseases. In this mini-review we will highlight some of the recent advances and discoveries in the field, with a particular focus on metabolic demands of Th17 cells and their implications for autoimmunity.